De que povo é a praça? Lambe-lambes, estúdios e discursos urbanizadores em Feira de Santana (1970-1985) - Gama, Kalila Catharine Oliveira (2017)
The dissertation has as object to analyze the occupation and appropriation of the "Bernardino Bahia Square" as a space for the construction of the professional work of the lambe-lambes photographers, undertaken in the early 1970's in the city of Feira de Santana. The intention is to understand the tensions born of the occupation of the square by the photographers lambe-lambes. For that, an analysis of the conjuncture that precedes the temporal cut - 1970-1985 is presented. The kickback is fundamental for the understanding about the rise of the county Feirense as a road junction and commercial warehouse, its insertion in the policy of decentralization of industries through fiscal incentives and the implications in the processes of urbanization and migration registered in the city. Throughout the text, will also be studied the representations forged by the newspapers Folha do Norte and Feira Hoje on the county Feirense, in agreement with the interests of certain groups. In addition, it seeks to understand how the determination of an ordering in the commercial center was carried out, by means of norms, like the Tax Code of 1963 and the Code of Postures of 1967. From the oral testimonies of three lambe-lambes photographers, it was possible to draw a scenario of the daily toil of these professionals, detailing the journey and the discipline of work, the photographic technique and the internal organization of the group. Finally, were examined the motivations for traveling photographers to occupy the square cited, the mechanisms used for the appropriation of the site and the tactics for maintenance in the public space; as well as the repercussions of this dynamic in the local press and in the municipal legislature, without neglecting the actions undertaken by the Municipal Government to alleviate conflicts.